THE IMPACT OF COMPENSATION AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT BPR KERTIAWAN GIANYAR BRANCH - I Gede Putu Kawiana (Jurnal Scientia, 2021)
The objective of this research is to examine how compensation and motivation impact the performance of employees at the Gianyar Branch of BPR Kertiawan. Employee performance is a crucial factor in accomplishing organizational objectives and sustaining competitiveness. Offering fair compensation and sufficient motivation can play a pivotal role in enhancing employee performance. The research employs a quantitative approach using surveys. The study's participants are randomly selected employees from BPR Kertiawan's Gianyar Branch. A questionnaire is employed to collect data, covering variables related to compensation, motivation, and employee performance. The research employs regression analysis to test its hypotheses.The findings reveal that compensation and work motivation have a positive and statistically significant impact on employee performance when examined individually. Furthermore, when considered together, compensation and motivation continue to significantly influence employee performance. The analysis of the coefficient of determination indicates that approximately 63.4% of the variations in performance can be attributed to compensation and motivation variables. The remaining 36.6% is influenced by factors that were not explored in this study.